Effect of Education on Service Quality of Service Industries - Adhikari, Yadav (Social Inquiry: Journal of Social Science Research, 2022)
The service sectors always focus to upgrade and improve the service quality when they pursue the new product or services to the customers. Based on the service quality literature, this paper assesses the five dimension of SERVQUAL model and make a gap analysis including antecedents of gaps and effects of education to mould the service quality in different organizational settings, most importantly in the service sector. To collect the information and knowledge on service quality, different service quality literature, practices as well as notions of the service delivery of different service sector is identified, reviewed, and conceptualized. The literature and different findings show that there is a positive and significant mediating effect of education that remains with service quality in the different organizational settings. Basically, in the service sector, quality service plays a vital role to the targeted customer for perceiving about the products or delivered services. Hence, the service provider is the major determinant factor for stretching the updated service quality ubiquitously to meet customer expectations.